Multimedia and Its Role in the Field of Teaching from the Perspective of Students in the Department of Art Education (Al-Academy, 2026)
The educational process has witnessed significant development due to technological advancement, making the use of multimedia in teaching an educational necessity. This study aims to explore the role of multimedia in teaching from the perspective of students in the Department of Art Education at the College of Fine Arts, University of Baghdad, for the academic year 2024–2025. The study adopted a descriptive-analytical approach and included a sample of 65 fourth-year students. A questionnaire prepared by the researchers was used for data collection. The results showed that students highly value the role of multimedia, with a mean score of 51.107 compared to the hypothetical average of 40, indicating a generally positive outlook. The findings also revealed that multimedia contributes to enhancing understanding and engagement without negatively affecting critical thinking. However, some questionnaire items showed varying opinions regarding the extent to which multimedia supports reading skills and information verification.